The molecular and isotopic effects of hydrothermal alteration of organic matter in the Paleoproterozoic McArthur River Pb/Zn/Ag ore deposit - Williford, Kenneth; Grice, Kliti; Logan, G.; Chen, J.; Huston, D. (Elsevier Science BV, 2011)
The molecular distribution and compound specific stable carbon and hydrogen isotope ratios were measured on solvent extractable hydrocarbons from the Late Paleoproterozoic McArthur River, or “Here's Your Chance” (HYC) Pb/Zn/Ag ore deposit in the Northern Territory of Australia. Five samples were collected from the McArthur River mine on a northeast–southwest transect in order to sample a gradient of hydrothermal alteration. One sample was taken from the unmineralized W-Fold Shale unit immediately below the HYC ore deposit. dD of n-alkanes, branched alkanes and bulk aromatic fractions were measured, and d13C of n-alkanes, polynuclear aromatic hydrocarbons (PAHs) and bulk kerogen were measured to assess the isotopic effects of a varying degree of hydrothermal alteration on different components of HYC organic matter (OM). Relative to n-alkanes in Barney Creek Formation sediments that did not undergo mineralization, HYC n-alkanes are enriched in deuterium (D) by 50–60‰. This is likely to be a result of equilibrium hydrogen exchange during ore genesis with a highly D-enriched fluid that originated in an evaporitic basin. Trends with distance along the sample transect are ambiguous, but from the northernmost to southernmost point, n-alkanes are less D-enriched, and PAHs are less abundant and less 13C-enriched. This could be due to decreasing hydrothermal alteration effects, decreasing delivery of highly altered OM by the mineralizing fluid, or both. The carbon isotopic composition of HYC PAHs is inconsistent with a Barney Creek Fm source, but consistent with an origin in the underlying Wollogorang Formation. PAHs are 13C-depleted relative to n-alkanes, reflecting a kerogen source that was 13C-depleted compared to n-alkanes, typical for Precambrian sediments. PAHs are more 13C-depleted with increasing molecular weight and aromaticity, strengthening the case for a negative isotopic effect associated with aromatization in ancient sediments. Together, these data are consistent with a an ore deposition model in which fluids originated in an evaporitic deposit lower in the basin and interacted with metals and OM in the Tawallah Group at temperatures above 250 °C and a depth of ~ 6 km before ascending along a flower structure associated with the Emu Fault and cooling to 200 ± 20 °C before reaching Barney Creek sediments.